Autism spectrum disorder recurrence, resulting of germline mosaicism for a CHD2 gene missense variant. Issue 6 (28th September 2017) - Lebrun, N.; Parent, P.; Gendras, J.; Billuart, P.; Poirier, K.; Bienvenu, T.
Abstract : Germline mosaicism for a novel missense variant p.Thr645Met located in the SNF2‐related ATP dependent helicase domain of CHD2 in 2 affected siblings with autism spectrum disorder.